A Conductive Nanowire‐Mesh Biosensor for Ultrasensitive Detection of Serum C‐Reactive Protein in Melanoma. (5th June 2018) - Lin, Zuan‐Tao; Li, Yaxi; Gu, Jianhua; Wang, Huie; Zhu, Zhuan; Hong, Xia; Zhang, Zijing; Lu, Qinqin; Qiu, Jingyi; Wang, Xifan; Bao, Jiming; Wu, Tianfu
Abstract: Detection of extracutaneous melanoma is still challenging and is of importance in improving survival rate. In this report, an ultrasensitive biosensor is constructed where a C‐reactive protein (CRP) aptamers based molecular recognition core and a conductive polypyrrole (PPy) nanowire mesh based signal amplifier are developed. The conductive PPy nanowire (less than 10 nm in diameter) mesh architecture is uniformly dispersed within polymeric matrix via template‐free in situ synthesis. Serum CRP levels are quantitatively analyzed through monitoring the conductance change caused by polymeric network shrinkage upon the aptamer‐CRP binding. The limit of detection (LOD) of the polymeric sensor for human CRP sample can reach 7.85 × 10 −19 m . This CRP‐specific biosensor and a commercial CRP enzyme‐linked immunosorbent assay (ELISA) kit are used to perform side‐by‐side measurement of serum CRP in melanoma patients. The results indicate that this conductive polymeric senor is highly sensitive and selective in accurately discriminating melanoma patients from healthy controls using serum CRP as a biomarker, which is further validated by a commercial human CRP ELISA kit. Collectively, this novel ultrasensitive nanowire‐based polymeric biosensor may hold promise in biomarker detection and diagnosis of cancer. Abstract : A novel polymeric biosensor with a C‐reactive protein (CRP) aptamers based molecular recognition core and a conductive polypyrrole (PPy) nanowire‐mesh based signal amplifier is developed. The PPy nanowire (<10 nm in diameter) mesh is dispersed within polymeric matrix via template‐free in situ synthesis. Serum CRP is quantified via monitoring the conductance change induced by polymeric network shrinkage upon CRP binding.